PELATIHAN BUDIDAYA SAYURAN HIRDOPONIK BAGI WARGA DESA DADAPAN KECAMATAN WAJAK - Rahayu, Yekti Sri; Kirnoprasetyo, Istiyono; Sulistyo, Mikael Adri Budi; Rukmana, Vita Maulidia; Firdaus, Rizalnur (Jurnal Likhitaprajna, 2024)
Most of the people in Dadapan Village have yards that have not been utilized optimally. The community also does not know the techniques for cultivating vegetable plants in the yard to fulfill household scale food security programs. This community service program aims to empower the community in Dadapan village, especially women from the PKK and Karang Taruna through the use of yard land for the production of vegetable crops. The implementation method applied is training in simple hydroponic vegetable farming which is carried out through the Real Work Lecture program. The activity stages begin with coordinating the implementation of the program with community leaders, training activities and practice of installing a hydroponic wick system in the yard. The results of the training activities showed that the community, especially PKK women and members of youth organizations, were able to cultivate vegetable plants in their yards using the wick system hydroponic planting technique. The wick system hydroponic planting technique is very popular with PKK women and youth organizations because the materials and equipment used are very easy to obtain, economical and easy to apply in the home garden. The practice of cultivating vegetables in the home yard using a hydroponic system can support the fulfillment of vegetable needs at the household level, supported by intensive maintenance of vegetable plants so that the home yard becomes more productive